Realization of real-time directional radiation of acoustic wave with non-uniform Mie resonators. (7th February 2022) - Lan, Jun; Wang, Tao; Zhao, Ying; Liu, Xiaozhou; Wan, Xili; Liu, Yunpeng; Wang, Zixuan; Li, Yifeng
Abstract : In this study, we present a tunable metamaterial consisting of rotatable non-uniform Mie resonators (NMRs) with identical structures. The metamaterial can in real-time manipulate the direction of acoustic radiation and guarantee high transmission efficiency by simply changing the rotation angle of the NMR unit cells, which is induced by the anisotropic property of NMR. In addition, according to generalized Snell's law, the arbitrarily direction-scanning capability is realized by tuning the phase shift distribution along the metamaterial. Our proposed anisotropic metamaterial could contribute to designing a device for the emission and reception of acoustic waves in real-time.